Is there life on Mars? [videorecording (DVD)] - Ritsko, Alan J.; Sanders, Jay O., 1953- (WGBH Boston Video, 2009)
This videodisc showcases the latest scientific revelations from a planet, once alien, now poised to reveal provocative new clues in the tantalizing quest to plumb its past for signs of water and, perhaps, even life.